The Effect of Deposition Parameters on Morphological and Optical Properties of Cu2S Thin Films Grown by Chemical Bath Deposition Technique - Honar S. Ahmed; Raghad Y. Mohammed (Photonics, 2022)
The chemical bath deposition technique has been used for the deposition of Cu2S thin films on glass substrates. The thickness of deposited thin films strongly depends on the deposition parameters. The present study revealed that the thickness increased from 185 to 281 nm as deposition time increased and from 183 to 291 nm as bath temperature increased. In addition, the thickness increased from 257 to 303 nm with the increment of precursors concentration and from 185 to 297 nm as the pH value increased. However, the thickness decreased from 299 to 234 nm with the increment of precursors concentration. The morphology of Cu2S thin films remarkably changed as the deposition parameters varied. The increase in deposition time, bath temperature, and CuSO4.5H2O concentration leads to the increase in particle sizes, homogeneity, compactness of the thin films, and the number of clusters, and agglomeration, while the increase in thiourea concentration leads to the decrease in particle sizes and quality of films. Optical results demonstrated that the transmission of thin films rapidly increased in the UV–VIS region at (λ = 350–500 nm) until it reached its maximum peak at (λ = 600–650 nm) in the visible region, then it decreased in the NIR region. The high absorption was obtained in the UV–VIS region at (λ = 350–500 nm) before it decreased to its minimum value in the visible region, and then increased in the NIR region. The energy bandgap of thin films effectively depends on the deposition parameters. It decreased with the increasing deposition time (3.01–2.95 eV), bath temperature (3.04–2.63 eV), CuSO4.5H2O concentration (3.1–2.6 eV), and pH value (3.14–2.75 eV), except for thiourea concentration, while it decreased with the increasing thiourea concentration (2.79–3.09 eV).